ALQUEVA HYDRO-METEOROLOGICAL EXPERIMENT (ALEX): FIRST RESULTS OF AQUATIC ECOLOGICAL ASSESSMENT - Novais, Maria Helena (2015)
The ALqueva hydro-meteorological EXperiment (ALEX) field campaign took place monthly during summer 2014 and consisted in in situ measurements and sampling of water and biological elements, collected from three fixed platforms placed in the lacustrine zone. This integrated overview, including meteorological, environmental and biological results contributes to improve the knowledge of the reservoir dynamics and therefore to propose adequate management measures to preserve the observed biological integrity.